Percutaneous balloon dilatation in a patient with membrane subaortic stenosis: a propos of a case - Mariño, Carlos (2013)
Discrete subaortic stenosis is a rare cardiac lesion with left ventricle outflow narrowed by the presence of a muscular or fibrous ring. It accounts for 8-20% of all forms of left ventricle outflow tract obstruction. Surgery is considered the treatment of choice when the peak gradient is over 50 mmHg or in patients with lower gradients and either progression of aortic regurgitation, dilated ventricular diameters, left ventricular dysfunction or symptoms. We report the case of a child with membrane subaortic stenosis and symptoms of heart failure and compromised left ventricular function, in whom percutaneous balloon dilatation was performed as an alternative to surgery. This is the first case reported in the country with successful outcome.